Identification of Noise Intensity Levels in the Turbine Area at PT X: Identification of Noise Intensity Levels in the Turbine Area at PT X - Fitri Aulia Aulia; Firman Edigan; Windya Bintang Auzasica; Muhammad Alam Daffa DE; Muhammad Nasirudin (Jurnal Pengabdian Kesehatan Komunitas, 2026)
Noise is one of the physical hazards that may affect occupational health and safety, particularly in industrial power generation areas. This Public Health Field Practice aimed to identify the level of noise intensity in the turbine area of PT X and provide recommendations for controlling the risk of noise exposure. The methods included field observation, brief interviews, noise measurement using a Sound Level Meter, priority problem identification using the non-scoring technique or Delbeq method, and risk analysis using the HIRADC approach. The measurement results showed that the noise level in the turbine area exceeded the threshold limit value, with a combined noise level of 96 dBA. This value was higher than the permitted threshold limit of 85 dBA for 8 hours of daily exposure based on the Indonesian Ministry of Manpower Regulation No. 5 of 2018. The main sources of noise included turbine operation, generators, pumps, high-pressure steam pipes, and room conditions dominated by hard and metallic materials. The intervention was conducted through educational posters and videos about the hazards of noise exposure and the importance of using hearing protection equipment. Continuous control efforts are needed through consistent use of personal protective equipment, periodic noise measurements, workers’ hearing examinations, and engineering controls such as the installation of sound-absorbing materials. Abstrak Kebisingan merupakan salah satu faktor bahaya fisik yang berpotensi menimbulkan gangguan kesehatan dan keselamatan kerja, terutama pada area industri pembangkitan listrik. Praktikum Kesehatan Masyarakat ini bertujuan untuk mengidentifikasi tingkat intensitas kebisingan pada area turbin PT X serta memberikan rekomendasi pengendalian risiko terhadap paparan kebisingan. Metode kegiatan dilakukan melalui observasi lapangan, wawancara singkat, pengukuran kebisingan menggunakan Sound Level Meter, penetapan prioritas masalah dengan metode non-scoring technique atau Delbeq, serta analisis risiko menggunakan pendekatan HIRADC. Hasil pengukuran menunjukkan bahwa tingkat kebisingan pada area turbin berada di atas Nilai Ambang Batas, dengan nilai kebisingan gabungan sebesar 96 dBA. Nilai tersebut melebihi NAB 85 dBA untuk paparan kerja 8 jam per hari berdasarkan Permenaker No. 5 Tahun 2018. Faktor penyebab kebisingan berasal dari pengoperasian turbin, generator, pompa, pipa uap bertekanan tinggi, serta kondisi ruangan yang didominasi material keras dan logam. Intervensi yang dilakukan berupa edukasi melalui poster dan video mengenai bahaya kebisingan serta pentingnya penggunaan alat pelindung pendengaran. Diperlukan pengendalian berkelanjutan melalui penggunaan APD secara konsisten, pengukuran kebisingan berkala, pemeriksaan pendengaran pekerja, serta penerapan rekayasa teknis seperti pemasangan peredam suara.